ABCC8 polymorphism (Ser1369Ala): influence on severe hypoglycemia due to sulfonylureas. (December 2010) - Sato, Ryosuke; Watanabe, Hiroshi; Genma, Rieko; Takeuchi, Masahiro; Maekawa, Masato; Nakamura, Hirotoshi
Aims: Sulfonylureas are categorized according to their binding sites of the ATP-sensitive K+ channel (KATP channel) complex in pancreatic β-cells. The binding sites are classified as A, B and A + B site (both A and B sites), respectively. The Ser1369Ala variant in the sulfonylurea receptor gene ABCC8 which encodes a subunit of the KATP channel complex has been demonstrated to be associated with the hypoglycemic effect of gliclazide, which binds to the A site. However, the hypoglycemic effect of the Ser1369Ala variant on treatment with A + B binding site sulfonylureas, such as glimepiride or glibenclamide, is still uncertain.Materials & methods: In a case–control study, 32 patients with Type 2 diabetes admitted to hospital with severe hypoglycemia and 125 consecutive Type 2 diabetic outpatients without severe hypoglycemia were enrolled. We determined the genotypes of the ABCC8 polymorphism (Ser1369Ala) in the patients with or without severe hypoglycemia. All of the patients were taking glimepiride or glibenclamide.Results: In the patients treated with glimepiride or glibenclamide, we found no significant differences in the distribution of the Ser1369Ala genotype between patients with or without severe hypoglycemia (p = 0.26). Moreover, the Ala1369 minor allele tended to be less frequent in the hypoglycemic group (31 vs 43%; OR: 1.65; 95% CI: 0.92–2.96; p = 0.09).Conclusion: Our findings suggest that the Ser1369Ala variant is not a major predictive factor of severe hypoglycemia due to glimepiride or glibenclamide, both of which bind to the A + B site. It is likely that severe hypoglycemia due to A + B binding site sulfonylureas will be mediated by other factors, and not the Ala1369 minor allele.